2018
DOI: 10.1016/j.biopsych.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Cannabinoid CB1 Receptors in Male Tobacco Smokers Examined With Positron Emission Tomography

Abstract: Tobacco-smoking healthy men have a widespread reduction of CB receptor density in brain. Reduction of CB receptors appears to be a common feature of substance use disorders. Future clinical studies on the CB receptor should control for tobacco smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…The current study did not find any sex‐related effects in either forced choice or the cue‐reactivity procedure. While previous research has shown a decrease in CB1R expression in male smokers that study did not compare males to female smokers (Hirvonen et al., 2018). At this point, there are limited studies investigating sex differences in the context of the CB1 system and nicotine dependence.…”
Section: Discussionmentioning
confidence: 86%
“…The current study did not find any sex‐related effects in either forced choice or the cue‐reactivity procedure. While previous research has shown a decrease in CB1R expression in male smokers that study did not compare males to female smokers (Hirvonen et al., 2018). At this point, there are limited studies investigating sex differences in the context of the CB1 system and nicotine dependence.…”
Section: Discussionmentioning
confidence: 86%
“…Tobacco use represents another potential confound, as subjects with psychiatric disorders tended to smoke at much higher rates than controls across studies (Supplemental Tables 1 and 2). A published abstract directly comparing CB 1 availability in smokers and non-smokers using [ 18 F]FMPEP-d 2 found that smokers had significantly lower CB 1 availability throughout the brain [107]. However, this contrasts with supplementary analyses performed in several published studies, which found that smoking status was not associated with CB 1 availability in individuals with comorbid psychopathology [39,41,52,53,64,74].…”
Section: Discussionmentioning
confidence: 96%
“…A sparse to a very low density of receptors was observed in regions such as the hypothalamus, basal amygdala, central gray, thalamus, and brainstem (Herkenham et al, 1990). In a wide range of preclinical and clinical positron emission tomography (PET) studies, altered availability of CB1 receptor has been shown in the context of psychiatric diseases, such as addictive disorders (Gérard et al, 2010;Hirvonen et al, 2012Hirvonen et al, , 2013Hirvonen et al, , 2018Neumeister et al, 2012;Ceccarini et al, 2013bCeccarini et al, , 2014Ceccarini et al, , 2015D'Souza et al, 2016), schizophrenia (Wong et al, 2010;Ceccarini et al, 2013a;Verdurand et al, 2014;Ranganathan et al, 2016), post-traumatic stress disorder (Neumeister et al, 2013;Pietrzak et al, 2014) and eating disorders (Addy et al, 2008;Gérard et al, 2011;Casteels et al, 2014;Ly et al, 2015;Ceccarini et al, 2016;Lahesmaa et al, 2018), furthermore in neurological diseases, such as Parkinson's disease (Casteels et al, 2010b,d;Van Laere et al, 2012;Ceccarini et al, 2019b), Huntington's disease (Casteels et al, 2010c(Casteels et al, , 2011Ooms et al, 2014;Ceccarini et al, 2019a) and epilepsy (Goffin et al, 2008(Goffin et al, , 2011Cleeren et al, 2018). A better understanding of the endocannabinoid system with its receptors will help to refine diagnostic and evidence-based therapeutic strategies for the treatment of associated disorders.…”
Section: Introductionmentioning
confidence: 99%